What is what in the nanoworld : a handbook on nanoscience and nanotechnology - Borisenko, Victor E. (Wiley-VCH Verlag GmbH, 2012)
"Summarizes the terms and definitions, most important phenomena, and regulations occurring in the physics, chemistry, technology, and application of nanostructures. A representative collection of fundamental terms and definitions from quantum physics and chemistry, special mathematics, organic and inorganic chemistry, solid state physics, material science and technology accompanies recommended secondary sources for an extended study of any given subject. Each of the more than 2,200 entries ... interprets the term or definition in question and briefly presents the main features of the phenomena behind it. Additional information in the form of notes ... supplements the entries and gives a historical perspective of the subject with reference to further sources"--